Congenital bilateral perisylvian syndrome: a rare cause of epilepsy - Sharma, Trishalla; Chauhan, Gauri; Duggal, Tegsimran; Bhardwaj, A. K. (International Journal of Contemporary Pediatrics, 2016)
Congenital bilateral perisylvian syndrome (CBPS) is an entity proven or diagnosed on basis of neuroimaging in the form of MRI (Magnetic Resonance Imaging). A case with classical triad of fascio- masticatory diplegia, epilepsy and mental retardation has been seen. We report a case of a 6 years old male child on intermittent treatment for seizures since 6 months presenting to us with abnormal movement, recurrent spitting and drooling of saliva with slurring of speech. Diagnosed on MRI with involvement of perisylvian location in temporal lobe. The etiology of epilepsy was justified and symptomatically treated.